The representation of external threats
1 online resource.
Keywords: In The Representation of External Threats , Eberhard Crailsheim and María Dolores Elizalde present a collection of articles that trace the phenomenon of external threats in a multitude of settings across Asia, America, and Europe. The scope ranges from military threats against the Byzantine rulers of the 7th century to the perception of cultural and economic threats in the late 19th century Atlantic, and includes conceptual threats to the construction of national histories. Focussing on the different ways in which such threats were socially constructed, the articles offer a variety of perspectives and interdisciplinary methods to understand the development and representations of external threats, concentrating on the effect of 'threat communication' for societies and political actors. Contributors are Anna Abalian, Vladimir Belous, Eberhard Crailsheim, María Dolores Elizalde, Rodrigo Escribano Roca, Simon C. Kemper, Irena Kozmanová, David Manzano Cosano, Federico Niglia, Derek Kane O'Leary, Alexandr Osipian, Pedro Ponte e Sousa, Theresia Raum, Jean-Noël Sanchez, Marie Schreier, Stephan Steiner, Srikanth Thaliyakkattil, Ionut Untea and Qiong Yu.